Effectiveness Of Structured Spiritual Care Models in Improving Psychological and Physiological Outcomes in Intensive Care Unit (ICU) Patients: A Systematic Review - Wirakhmi, Ikit Netra; Purnawan, Iwan (Media Publikasi Cendekia Indonesia, 2025)
Despite their critical role in patient well-being, spiritual needs are often overlooked in intensive care settings. Addressing these needs through structured interventions may improve patients' psychological and physiological outcomes in Intensive Care Unit (ICU). This systematic review aims to identify and evaluate various spiritual care models implemented in ICU settings and their impact on patient outcomes. A systematic search was conducted across six databases (PubMed Central, ScienceDirect, Sage Journals, Cambridge Core, Cochrane Library, and ProQuest) for studies published up to 2023. Eligible studies met the following criteria: (i) experimental design, (ii) spiritual care interventions, and (iii) ICU implementation. The screening process was conducted in two phases: title and abstract screening, followed by full-text assessment, with methodological quality evaluation. A total of 6,975 articles were identified, and 11 studies involving 842 participants met the inclusion criteria. Three distinct spiritual care models were identified: Chaplain-led picture-guided spiritual care, HeartTouch Technique, and Islamic-based spiritual care. Chaplain-led picture-guided spiritual care was particularly effective in reducing anxiety, while Islamic-based spiritual care, particularly Quran recitation, demonstrated significant benefits in reducing stress and promoting emotional well-being. These interventions demonstrated significant benefits, including reductions in stress and anxiety (reported in 4/11 studies), improvements in well-being (3/11 studies), and decreased feelings of isolation (2/11 studies). No significant adverse effects were reported. Spiritual care interventions in ICU settings provide psychological and emotional benefits for patients, reducing anxiety, stress, and isolation.